Efeito da associação da dieta, do ômega três, e de antioxidantes em cães portadores de doença renal crônica - Pillar Gomide do Valle (2014)
In order to evaluate the contribution of the drug combination of omega 3, vitamin E, sodium selenite, copper gluconate, zinc gluconate, chondroitin sulfate and glucosamine (Gerioox®), twelve dogs from the outpatient service of the Veterinary Hospital UFMG, suffering from chronic kidney disease (CKD), were studied. Were performed exams blood count and measurement of serum calcium, phosphorus, glucose, urea and creatinine, urinalysis, urine protein creatinine ratio and glomerular filtration rate (GFR) before starting the experiment (T0), after 30 (T1), 90 (T2) and 120 days (T3). There was a negative correlation (P <0.05) between the GFR and urinary protein creatinine ratio and GFR and serum urea and creatinine. There was improvement in clinical status of patients studied signaling observed by tutors informing improves vitality and appetite and the clinical observations of improved overall health status, coat and parameters. According to the results obtained for the conditions for this experiment, it can be concluded that combination therapy based omega 3 (Gerioox®), improves the general condition of patients with CKD, improves renal excretion and not cause increased glomerular pressure.